The Search for Pure Water in Ottawa: 1910-1915 - Warfe, Chris (Urban History Review / Revue d'histoire urbaine, 1979)
In the second decade of the twentieth century, concern over the purity of Ottawa's water supply, heightened by a series of typhoid epidemics, led to protracted efforts by certain social elites to provide alternatives. None were successful. But when the pure water question intersected with a problem of supply that impaired the capacity to fight fires and consequently drove up insurance rates, the business community became engaged. An immediate solution was found. The provision of pure water in Ottawa was, in effect, a product of economic imperatives, not health needs.